Multicultural Education in Slovakia: Perspectives and Risks - Peter Kondrla (Peoples' Friendship University of Russia (RUDN University), 2021)
The article analyses 20 years of experience with multicultural education in Slovakia. The starting point is to examine the causes and reasons why multicultural education has been included in the education system. The rationale for the introduction of multicultural education is interpreted in the context of the current possibilities and needs of society, identifying mainly the problems that multicultural education solves today. The basic principles and pillars of multicultural education are introduced and at the same time their strengths and weaknesses are examined. Emphasis is placed on human dignity and social responsibility as sources on which other values of multicultural education are based. In contrast to these principles is the environment in which education takes place. The school and family environment do not offer a sufficient principled background, do not prefer and often do not respect the values of multiculturalism. The resulting conflict of principles and environment poses the biggest problem and risk in multicultural education. Specific attention is paid to the issue of education in the mother tongue, this problem in Slovakia mainly affects the Roma minority. The inability to learn in ones mother tongue is contrary to equal opportunities as well as to the possibilities for the development of the human person in the context of his or her dignity. Finding perspectives requires a change from above, in the setting of the school environment as well as a change from below, i.e. a change in the value orientations and personal attitudes of individual teachers and changes in their preparation for the future profession.